Influencing factors and environmental effects of interactions between goethite and organic matter: A critical review - Yi, Shuqi; Chen, Xiaorui; Cao, Xu; Yi, Bing; He, Wei (Frontiers in Environmental Science, 2022)
This paper reviews progresses in the interactions between goethite and organic matter (OM) and their environmental effects in recent decades. The interactions mainly include the effect of organic matter on the surface properties and the crystallization of goethite, molecular changes of OM caused by goethite, and their interaction mechanisms, which can be depicted by the commonly used Langmuir model, the charge distribution multi-site complexation model (CD-MUSIC model), ligand charge distribution model (LCD model), and natural organic matter charge distribution model (NOM-CD model). The influencing factors of the interactions are summarized with emphasis on the external, including pH, ionic strength, carbon dioxide (CO2), and the internal, including the structure of OM and iron species. The goethite—OM complexes caused by the interactions will affect migration and transformation of conventional heavy metals and emerging antibiotics. The complexes, as the carrier of carbon and iron, are also the critical parts of the carbon and iron cycles, which are associated with climate change. This review provides a basis for future mechanism studies of formation, transformation, and effects of goethite—OM complexes (particulate OM or carbon-contained minerals) in different environmental systems at a molecular level.